RomA, A Periplasmic Protein Involved in the Synthesis of the Lipopolysaccharide, Tunes Down the Inflammatory Response Triggered by Brucella. (6th January 2018) - Valguarnera, Ezequiel; Spera, Juan M; Czibener, Cecilia; Fulgenzi, Fabiana R; Casabuono, Adriana C; Altabe, Silvia G; Pasquevich, Karina A; Guaimas, Francisco; Cassataro, Juliana; Couto, Alicia S; Ugalde, Juan E
Abstract: Brucellaceae are stealthy pathogens with the ability to survive and replicate in the host in the context of a strong immune response. This capacity relies on several virulence factors that are able to modulate the immune system and in their structural components that have low proinflammatory activities. Lipopolysaccharide (LPS), the main component of the outer membrane, is a central virulence factor of Brucella, and it has been well established that it induces a low inflammatory response. We describe here the identification and characterization of a novel periplasmic protein (RomA) conserved in alpha-proteobacteria, which is involved in the homeostasis of the outer membrane. A mutant in this gene showed several phenotypes, such as membrane defects, altered LPS composition, reduced adhesion, and increased virulence and inflammation. We show that RomA is involved in the synthesis of LPS, probably coordinating part of the biosynthetic complex in the periplasm. Its absence alters the normal synthesis of this macromolecule and affects the homeostasis of the outer membrane, resulting in a strain with a hyperinflammatory phenotype. Our results suggest that the proper synthesis of LPS is central to maximize virulence and minimize inflammation. Abstract : RomA is a periplasmic small protein of Brucella abortus with no known function and conserved among alpha-proteobacteria. We demonstrate that RomA is involved in the biosynthesis of the lipopolysaccharide and necessary to counterbalance virulence and inflammation.